Publication Trends of Computational Thinking in Elementary School Students: A Bibliometric Review - Majid Majid; Franky A Oroh; Perry Zakaria; Swasti Maharani; Adriyanto Moha (STAI Hubbulwathan Duri, 2025)
This study investigates publication trends, citation trends, keyword distribution, and novelty potential in research on computational thinking (CT) in elementary schools over the past decade. It conducted a bibliometric analysis of English articles and proceedings published between 2015 and 2024. Data sources included academic databases, with article selection based on defined inclusion criteria. Bibliometric techniques such as co-citation analysis and keyword co-occurrence were utilized to explore trends and patterns. The number of publications on CT in elementary education has increased significantly, particularly in 2021 and 2023. Citation analysis revealed a variety of research focuses, with clusters highlighting the growing prominence of specific topics. The integration of games as a tool for teaching CT is a notable trend, with research emphasizing game design, effectiveness evaluation, and curricular applications. Keyword distribution reflects diverse methods and approaches to teaching CT in elementary settings. The findings underscore the growing interest in CT research for primary education and its evolving focus on innovative strategies, particularly educational games. Future trajectories suggest continued exploration in this area, with implications for curriculum design and teacher training. This study provides a comprehensive overview of trends in CT research in elementary schools, offering insights for educators, policymakers, and researchers. Further work is needed to explore the practical integration of CT through innovative approaches, including games, to advance primary education.